Multiple cutaneous reticulohistiocytosis with T‐cell large granular lymphocyte clonopathy. (4th April 2017) - Papadantonakis, Pavlos; Kaparou, Maria; Papadaki, Helen A; Marinos, Leonidas; Krasagakis, Konstantin
Abstract: A 63‐year‐old Caucasian man presented with a 4‐month history of disseminated asymptomatic reddish‐brown papulonodular lesions. A skin biopsy showed dermal infiltration with CD68 + histiocytes, predominantly with eosinophilic cytoplasm, some with a ground‐glass cytoplasm, and a small number of giant cells. The diagnosis of multiple cutaneous reticulohistiocytosis was made. Bone marrow immunophenotyping due to peripheral blood lymphocytosis revealed the presence of a monoclonal population of CD3 +, CD8 + CD57 + large granular lymphocytes. The present case suggests the coexistence of multiple cutaneous reticulohistiocytosis with an underlying disorder.